Drilling characteristics optimization of polymer composite fortified with eggshells using box-Behnken design and zebra optimization algorithm - B. Deepanraj; A.M. Saravanan; N. Senthilkumar; Abdul Aziz Afzal; Abdul Rahman Afzal (Results in Engineering)
This study investigates the drilling characteristics of eggshell powders (ESPs) reinforced in delrin polymer composite. ESPs are obtained from the waste shells of eggs that are crushed, ground, and sieved to obtain a uniform size of 100 µm. ESPs are added to the delrin polymer in varying proportions (10-30 %) by weight, and the polymer composite is fabricated using injection molding. Box-Behnken design (BBD) is adopted for planning the experiments for varying values of rotational speed (RS), feed rate (FR), and % ESP. Drilling studies on the fabricated delrin+ESPs (DESP) are carried out using an uncoated carbide drill bit in a vertical machining center (VMC), and the surface roughness (SR) and material removal rate (MRR) are measured for further analysis. Observation shows that with higher RS and FR, the MRR and SR increase. With higher inclusion of ESP, the mechanical strength increases, which lowers the MRR and produces better SR. Desirability analysis provides the multi-criteria optimization, making an ideal condition of 912.14 rpm of RS, 0.054 mm/rev of FS, and 24.25 % ESP addition, which predicts an MRR of 0.274 mm3/min and SR of 3.102 µm. A bio-inspired metaheuristic algorithm, zebra optimization algorithm (ZOA), is adopted to maximize MRR and minimize SR, producing an ideal condition of 1000 rpm of RS, 0.02 mm/rev of FS, and 30 % ESP addition. The confirmation experiment with RSM-based optimal conditions presents an improvement in MRR of 2.46 % and an SR reduction of 23.25 %. In contrast, ZOA ideal conditions provide an increase in MRR by 1.06 % and a decrease in SR by 28.62 %.